2020
DOI: 10.1111/zph.12718
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated withEchinococcus multilocularisinfection in coyotes in southern Ontario

Abstract: Echinococcus multilocularis was recently reported in wild canids across southern Ontario, a newly recognized endemic area in Canada. In such areas, a comprehensive understanding of factors associated with infection in definitive hosts (wild canids) is critical for mitigating risk of transmission to humans. However, little is known about the transmission dynamics of the parasite in definitive hosts for this region. A study was therefore carried out to investigate the association of host‐level (sex, body conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Positive (+ corr) and negative (− corr) correlations of ecological drivers with the occurrence, prevalence or intensity of infection with E. multilocularis are reported, together with asymptotic, unimodal or other (Assoc) relationships. Numbers indicate the following references: 1 Staubach et al, 2001 , 2 Stieger et al, 2002 , 3 Hansen et al, 2004 , 4 Pleydell et al, 2004 , 5 Miterpakova et al, 2006 , 6 Fuglei et al, 2008 , 7 Casulli et al, 2010 , 8 Raoul et al, 2010 , 9 Stien et al, 2010 , 10 Burlet et al, 2011 , 11 Robardet et al, 2011 , 12 Tolnai et al, 2013 , 13 Guerra et al, 2014 , 14 Takeuchi-Storm et al, 2015 , 15 Miller et al, 2017 , 16 Otero-Abad et al, 2017 , 17 Bastien et al, 2018 , 18 Botero-Cañola et al, 2019 , 19 Mori et al, 2019 , 20 Kotwa et al, 2020 , 21 Avcioglu et al, 2021 , 22 Cenni et al, 2023 , 23 Mori et al, 2023 . The spatial scale(s) of the studies that report an association with a given factor is/are also reported.…”
Section: Resultsmentioning
confidence: 99%
“…Positive (+ corr) and negative (− corr) correlations of ecological drivers with the occurrence, prevalence or intensity of infection with E. multilocularis are reported, together with asymptotic, unimodal or other (Assoc) relationships. Numbers indicate the following references: 1 Staubach et al, 2001 , 2 Stieger et al, 2002 , 3 Hansen et al, 2004 , 4 Pleydell et al, 2004 , 5 Miterpakova et al, 2006 , 6 Fuglei et al, 2008 , 7 Casulli et al, 2010 , 8 Raoul et al, 2010 , 9 Stien et al, 2010 , 10 Burlet et al, 2011 , 11 Robardet et al, 2011 , 12 Tolnai et al, 2013 , 13 Guerra et al, 2014 , 14 Takeuchi-Storm et al, 2015 , 15 Miller et al, 2017 , 16 Otero-Abad et al, 2017 , 17 Bastien et al, 2018 , 18 Botero-Cañola et al, 2019 , 19 Mori et al, 2019 , 20 Kotwa et al, 2020 , 21 Avcioglu et al, 2021 , 22 Cenni et al, 2023 , 23 Mori et al, 2023 . The spatial scale(s) of the studies that report an association with a given factor is/are also reported.…”
Section: Resultsmentioning
confidence: 99%
“…We did not detect E . multilocularis in Québec, despite sampling several potential definitive host species (coyotes, red/arctic foxes, wolves) within a few hundred kilometers of health regions in Ontario where infected canids were detected [ 3 ]. Although this distance is well within the migratory limits of such canids [ 29 ], it is possible that our availability sampling technique was not ideal for detection, as we collected no canids directly along the provincial border.…”
Section: Discussionmentioning
confidence: 99%
“…multilocularis at its western and eastern distributional limits in Canada, and the novel identification of E . canadensis G8 in moose in Maine [ 2 , 3 ]. The Echinococcus genus is a group of cestodes maintained by specific predator-prey host assemblages in a wide range of geographic and climatic locales around the world [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations